2011
DOI: 10.1016/j.virol.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of dengue virus nonstructural protein 4B in monocytes enhances production of dengue hemorrhagic fever-associated chemokines and cytokines

Abstract: High levels of viremia and chemokines and cytokines underlie the progression of severe dengue disease. Dengue virus (DENV) preferentially infects peripheral blood monocytes, which secrete elevated levels of immunomediators in patients with severe disease. Further, DENV nonstructural proteins (NS) are capable of modifying intracellular signaling, including interferon inhibition. We demonstrate that peak secretions of immunomediators such as IL-6, IL-8, IP-10, TNFα or IFNγ in DENV-infected monocytes correlate wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 84 publications
2
31
0
Order By: Relevance
“…Antibody-induced signal transduction is a common feature of GPI-linked proteins [53,54,55] and this was found to happen with NS1, being another possible determinant that contributes to cellular activation, cytokine storm, and dengue pathogenesis [51]. Regarding other DENV NSPs, the expression of NS5 was shown to promote the induction of IL-8 expression and secretion in HEK293-transfected cells [56], and both NS5 and NS4B induce the secretion of immunomediators in THP-1 monocytes, being this action enhanced when NS4B is linked to the 2K peptide [57]. In addition, it was observed that the conditioned media of 2K-NS4B-transfected THP1 cells contained IL-8 and TNFα in levels that induce endothelial cell permeability and increased expression of adhesion molecules [58].…”
Section: Participation Of Denv Nsps In Dengue Physiopathologymentioning
confidence: 99%
“…Antibody-induced signal transduction is a common feature of GPI-linked proteins [53,54,55] and this was found to happen with NS1, being another possible determinant that contributes to cellular activation, cytokine storm, and dengue pathogenesis [51]. Regarding other DENV NSPs, the expression of NS5 was shown to promote the induction of IL-8 expression and secretion in HEK293-transfected cells [56], and both NS5 and NS4B induce the secretion of immunomediators in THP-1 monocytes, being this action enhanced when NS4B is linked to the 2K peptide [57]. In addition, it was observed that the conditioned media of 2K-NS4B-transfected THP1 cells contained IL-8 and TNFα in levels that induce endothelial cell permeability and increased expression of adhesion molecules [58].…”
Section: Participation Of Denv Nsps In Dengue Physiopathologymentioning
confidence: 99%
“…After cloning and verification of the correct orientation, the resulting plasmid can be purified and used directly for transfection into mammalian cells [7,8,9]. …”
Section: Methodsmentioning
confidence: 99%
“…The responses were associated with both MHC-I-and MHC-II-restricted epitopes, recognized by CD8 ϩ and CD4 ϩ T cells, respectively. Such T cell-based response patterns are usually observed after endogenous protein expression and are not expected to be found in animals immunized with nonadjuvanted protein (43). Further studies will address the inherent high immunogenicity of the NS5 and its capability to trigger cross-presentation to CD8 ϩ T cells by antigen-presenting cells.…”
Section: Figmentioning
confidence: 99%
“…Recently, subjects receiving a live attenuated tetravalent dengue vaccine developed T cell responses to highly conserved epitopes in the NS5 (34). Moreover, it has recently been demonstrated that protective immunity against DENV experimentally induced using live viruses in mice is achieved mainly by CD8 ϩ T cells targeting NSs, particularly NS5 (43). These studies indicate that the NS5 protein is a promising candidate antigen for a dengue vaccine formulation based on nonstructural proteins.…”
mentioning
confidence: 99%